The Valuation of Popular Theatre Performances: The Forgotten Success Story of Ljungby horn - Hoogland, Rikard (Nordic Theatre Studies, 2018)
Albert Ranft started as an actor in touring theatre companies in the 1880’s, but soon became responsible for one of the most important groups. Twenty-five years later, he ran a big company with about 2500 employees, owned theatres in Stockholm and Gothenburg as well as a couple of touring companies. His repertoire was based on popular entertainment plays, revues, operettas, historical plays, contemporary dramas etc. Simultaneously, his companies could offer ‘highbrow’ and ‘lowbrow’ productions. Even the actors could, during just one week, work in different genres. The way of programing was for Ranft an art form by itself, and sometimes he even acted in and directed the plays. In November 1893, at Stora Teatern in Gothenburg, he premiered a fairy tale play, and the staging was filled with spectacular effects. The play was, from the beginning, a stunning success with the production running for several hundred nights. Moreover, the production of Ljungby Horn became the ground stone for Ranft’s theatrical enterprise. The article describes how this success was established through mediatization and its base on rural oral history. The performance is analyzed and discussed as a popular theatre production (McConachie, Price, Röttger, Schecter). The author proposes that a more inclusive definition of popular theatre should be used; one which also takes into account the productions that had commercial success. Popular theatre needs to be included in theatre history writing to enable a better understanding of how the theatre system has developed.